Ubiquitination of alpha-synuclein in Lewy bodies is a pathological event not associated with impairment of proteasome function. - Tofaris, G; Razzaq, A; Ghetti, B; Lilley, K; Spillantini, MG (2003)
Lewy bodies are intracellular fibrillar inclusions composed of alpha-synuclein. They constitute the pathological hallmark of Parkinson's disease, dementia with Lewy bodies, and other neurodegenerative diseases. Although the majority of Lewy bodies are stained for ubiquitin by immunohistochemistry, the substrate for this modification is poorly understood. Insoluble, urea-soluble alpha-synuclein was separated from soluble fractions and subjected to two-dimensional gel electrophoresis to further characterize pathogenic alpha-synuclein species from disease brains. By using this approach, we found that in sporadic Lewy body diseases a highly modified, disease-associated 22-24-kDa alpha-synuclein species is ubiquitinated. Conjugation of one, two, and, to a lesser extent, three ubiquitins was detected. This 22-24-kDa alpha-synuclein species represents partly phosphorylated protein. Furthermore, no generalized impairment of the proteolytic activity of the proteasome was detected in brain regions with Lewy body pathology. Because unmodified alpha-synuclein is degraded by the proteasome in a ubiquitin-independent manner, these data suggest that accumulation of modified 22-24-kDa alpha-synuclein is a disease-specific event which may overwhelm the proteolytic system, leading to aberrant ubiquitination. Accordingly, carboxyl-terminal-truncated alpha-synuclein, presumably the result of aberrant proteolysis, is found only in association with alpha-synuclein aggregates.